After Tendulkar : the new stars of Indian cricket - Soumya Bhattacharya (Aleph, 2015)
Indian cricket has the most exciting young batting line-up in the world today. Virat Kohli, Shikhar Dhawan, Cheteshwar Pujara, Rohit Sharma and Ajinkya Rahane, led by their captain, M. S. Dhoni, have routinely destroyed international bowling attacks. While the young bowlers in the team lack the burgeoning reputation of the batters, they have shone in flashes at home and abroad. The current and future brilliance of the members of this team is all the more remarkable when you consider their youth, relative inexperience and the fact that they are following in the footsteps of the golden generation-arguably the set of finest cricketers this country has produced: Sachin Tendulkar, Sourav Ganguly, Rahul Dravid, V.V.S. Laxman and Anil Kumble.